Enhancing User Experience in Learning Environments: a Narrative Gamification Framework for Education - Palomino, Paula (2024)
This research explores the fertile intersection of narrative, gamification, and education, focusing on user experience (UX). Addressing a critical gap in the literature, we developed and validated a Narrative Gamification Framework for Education. The framework provides educators with tangible guidelines to gamify their lessons, emphasizing the content’s gameful transformation rather than the environment. The research contributes novel insights and practical tools to the fields of Human-Computer Interaction (HCI) and UX, with implications for the broader context of education. Our findings set the stage for future research, including an ongoing initiative to adapt the framework to engage teachers in a journey of recognition and learning.